(untitled) (Research, Society and Development, 2024)
Selection different microorganisms and substrates are important challenges to enable potential waste for animal feed. Therefore, the aim of the study was to evaluate semisolid fermentation (SSF) effects from fungus Lentinus tigrinus on protein enrichment and fibrous fractions degradation in different agro-industrial residues for animal feed. The strains were subcultured for 7 days until visible mycelium growth and subsequently substrates inoculated. Five types of agro-industrial residues were used as substrate: sugarcane bagasse, sisal coproduct, sisal coproduct dry, dry brewery residue and wet brewery residue. Substrate samples without innocuous and after FSS were collected for bromatological analysis in triplicate. The Dry Matter contents did not show great loss rates during the 24-hour period, maintaining a very close value to the initial one in all residues. Protein enrichment was observed in the five types of agro-industrial residues studied using SSF by L. tigrinus, with emphasis on the wet brewery residue, 50%. It was also in this substrate that there was a significant lignin reduction (17%) under the established conditions. All residues from this study can be used as a substrate for protein enrichment and animal feed destined. However, the brewery residue and the sisal coproduct, in the different evaluated forms, stood out.